Value of sprinkling feedlot cattle during heat - D.R. Ames; C. Willms (Kansas Agricultural Experiment Station Research Reports, 1977)
Four lots of growing-finishing cattle were sprinkled when dry bulb temperature exceeded 80 F the summer of 1976 and compared with lots not sprinkled. Sprinkled lots gained significantly (P<.01) more (1.20 kg per day compared with 1.04) (2.64 vs. 2.29 lbs.) than controls. Sprinkling also improved feed efficiency (F/G).
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Sprinkling cattle; Feed efficiency; Gain